Transformasi Partisipasi Masyarakat dalam Perencanaan Pembangunan Desa atas Penyusunan RPJMDes di Desa Mutiara Kabupaten Boalemo - Rizki Ntou, Mohamad; I. Rahim, Erman; Hamid Tome, Abdul (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
Community participation in village development planning is often only symbolic and does not reflect substantive involvement. This study aims to examine the level of community participation in the process of preparing the Village Medium-Term Development Plan (RPJMDes) in Mutiara Village, Paguyaman District, Boalemo Regency, and to identify factors that influence the low level of community involvement in the planning stage. The approach used is empirical law with qualitative methods. Data were obtained through direct interviews with village officials, community leaders, and community groups, as well as field observations of the dynamics of the preparation of the RPJMDes document. This study is also supported by secondary data in the form of laws and regulations and village planning documents. The results of the study indicate that community participation in the preparation of the RPJMDes in Mutiara Village is still a formality and has minimal substantive involvement. Planning meetings are generally only attended by limited representatives, with residents tending to be passive and not actively involved in the program review process. The main factors influencing low participation include the lack of understanding of the community and village government regarding the urgency of participation, limited involvement of community groups as a whole, and time constraints because activities are carried out when the majority of residents are working. Therefore, an adaptive and inclusive participatory approach is needed, as well as a more effective communication strategy so that the village development planning process truly reflects the needs and aspirations of the community. The results found that community participation in Mutiara Village was still low due to minimal understanding, time constraints, and lack of comprehensive group involvement.